Multiple Roles for Chemokines in Neutrophil Biology - Capucetti, Arianna; Albano, Francesca; Bonecchi, Raffaella (Frontiers in Immunology, 2020)
Chemokines are recognized as the most critical mediators for selective neutrophil recruitment during inflammatory conditions. Furthermore, they are considered fundamental regulators of neutrophil mobilization from the bone marrow (BM) to the bloodstream and for their homing back at the end of their life for apoptosis and clearance. However, chemokines are also important mediators of neutrophil effector functions including oxidative burst, degranulation, neutrophil extracellular trap (NET)osis, and production of inflammatory mediators. Neutrophils have been historically considered as a homogeneous population. In recent years, several maturation stages and subsets with different phenotypic profiles and effector functions were described both in physiological and pathological conditions such as infections, autoimmunity, and cancer. The aim of this review is to give an overview of the current evidence regarding the role of chemokines and chemokine receptors in neutrophil biology, including their possible role in neutrophil maturation, differentiation, and in defining emerging neutrophil subsets.